2018
DOI: 10.1088/1751-8121/aaccb4
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic operator relations and Bethe equations for spin-1/2 Richardson–Gaudin models

Abstract: In this work we demonstrate how one can, in a generic approach, derive a set of N simple quadratic Bethe equations for integrable Richardson-Gaudin (RG) models built out of N spins-1/2. These equations depend only on the N eigenvalues of the various conserved charges so that any solution of these equations defines, indirectly through the corresponding set of eigenvalues, one particular eigenstate.The proposed construction covers the full class of integrable RG models of the XYZ (including the subclasses of XXZ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…still commute with one another therefore defining an integrable model allowing us to retain the major simplifications that integrability has to offer. Our numerically study of the model's eigenstates makes use of recent work [28,29,33] which has shown explicitly that the set of eigenvalues (r 1 , r 2 . .…”
Section: Richardson-gaudin Modelsmentioning
confidence: 99%
“…still commute with one another therefore defining an integrable model allowing us to retain the major simplifications that integrability has to offer. Our numerically study of the model's eigenstates makes use of recent work [28,29,33] which has shown explicitly that the set of eigenvalues (r 1 , r 2 . .…”
Section: Richardson-gaudin Modelsmentioning
confidence: 99%
“…(7) was given in Ref. 11. Hence at least in the case when all the j p = 1/2, all the higher powers of h p can be written as multi-linear combinations of h p s. Here we derive similar expressions for higher values of j p .…”
Section: Introductionmentioning
confidence: 60%
“…For all of the models parametrised by (2), it was shown [28] that integrability is sufficient to establish that the resulting N conserved charges obey, at the operator level, the following quadratic relations:…”
Section: The Modelsmentioning
confidence: 99%
“…While similar constructions are possible for higher spins s > 1/2 (see [20] for example), they must contain additional local terms which takes them outside of the class of RG models studied here which is assumed to only contain S x i S x j , S y i S y j and S z i S z j coupling terms between spins i and j. It was recently demonstrated that, for these spin-1/2 systems in an external field, the conserved charges systematically obey quadratic relations so that the eigenvalues characterising their eigenstates can always be found as the solutions to a small set of quadratic equations [28]. Expectation values of local spin operators, in any of these eigenstates, can then also be computed easily by making use of the Hellmann-Feynman theorem giving access to some of the physics of these systems [29].…”
Section: Introductionmentioning
confidence: 99%